PENERAPAN PEMBELAJARAN NILAI-NILAI YANG TERINTEGRASI DALAM MATA PELAJARAN MATEMATIKA - Harry Soeprianto (Educatio, 2009)
Mathematics was giving contribution on tehnology and sciences. Mathematics was not only aritmatic but also contibut on life value which was important for people life. Life value consist of useful and simple value, discipline value, culture value, recreation value, estetic value and democratic value. The integration life value on mathematics instructional was not efectif . Keyword: Life Value